Historia y presente: "La larga agonía de la Argentina peronista", de Tulio Halperin Donghi. Ed. Ariel, Buenos Aires, 1998. 142 págs. - Gorgal, Diego Pablo (1998)
Fil: Gorgal, Diego Pablo. Pontificia Universidad Católica Argentina; Argentina